Carcass quality traits in four different crossbreds developed for backyard poultry and the effect of age on carcass quality under intensive system of rearing - PADHI, M K; CHATTERJEE, R N (The Indian Journal of Animal Sciences, 2013)
Present study was undertaken to evaluate male birds of 4 different crossbreds chicken (PD1 × PD4 (A), PD1 × PB2(B), PD1 × PD3 (R), PD1 × IWI (W)) for different carcass quality parameters at 10 and 18 weeks of age. At 10 and 18 weeks of age 8 and 6 birds each from each genetic group, respectively, were sacrificed to measure different carcass quality traits. Effects of age on each genetic group in respect to different carcass quality traits were also studied. All the traits on weight basis differed significantly between the genetic groups at 10 weeks of age. However, at 18 weeks of age pre slaughter body weight, shank, gizzard, giblet weight and all the cut up parts weight differed significantly. At 10 weeks of age statistical significance between different genetic groups was observed for feather, head, shank, eviscerated yield, liver, gizzard, abdominal fat and giblet%. Abdominal fat% was lowest in A. At 18 weeks of age head, shank, eviscerated and liver% differed significantly between genetic groups. Highest eviscerated% was obtained in B with lowest abdominal fat. Age effect was significant for eviscerated yield, liver, gizzard and abdominal fat in B. In R head, shank, liver, gizzard and giblet% reduced significantly at 18 weeks of age. Cut up parts percentage expressed as % of eviscerated weight showed significant difference between genetic groups for legs % at 10 weeks of age. Age showed significant effect for back and legs % in A and B, whereas R and W showed significant effect of age for neck and legs % and back and neck %, respectively. The results indicated that genetic groups and age significantly affect different carcass quality traits and B male recorded better eviscerated yield compared to other genetic groups. Legs cut% increases with increase of slaughter age.